2018
DOI: 10.3390/molecules23061453
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Mycobacterium tuberculosis Activity of Esters of Quinoxaline 1,4-Di-N-Oxide

Abstract: Tuberculosis continues to be a public health problem in the world, and drug resistance has been a major obstacle in its treatment. Quinoxaline 1,4-di-N-oxide has been proposed as a scaffold to design new drugs to combat this disease. To examine the efficacy of this compound, this study evaluates methyl, ethyl, isopropyl, and n-propyl esters of quinoxaline 1,4-di-N-oxide derivatives in vitro against Mycobacterium tuberculosis (pansusceptible and monoresistant strains). Additionally, the inhibitory effect of est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In fact, the majority of methyl esters (represented by circles) are located below the activity cut-off in Figure 3, with the exception of highly lipophilic compounds, e.g., PC-l-OBn-Ser-Me, PC-d/l-Pgl-Me. The effect of growing activity with the lengthening of the ester carbon chain had previously also been observed in derivatives of POA [21,23] or other antimycobacterial compounds [55] and it has been attributed to the above-mentioned better penetration inside the mycobacteria. However, as discussed later, other effects-as stereochemistry-seem to play an important role in structure-activity relationships in our compounds.…”
Section: Stereochemical Aspects Of Activitymentioning
confidence: 63%
“…In fact, the majority of methyl esters (represented by circles) are located below the activity cut-off in Figure 3, with the exception of highly lipophilic compounds, e.g., PC-l-OBn-Ser-Me, PC-d/l-Pgl-Me. The effect of growing activity with the lengthening of the ester carbon chain had previously also been observed in derivatives of POA [21,23] or other antimycobacterial compounds [55] and it has been attributed to the above-mentioned better penetration inside the mycobacteria. However, as discussed later, other effects-as stereochemistry-seem to play an important role in structure-activity relationships in our compounds.…”
Section: Stereochemical Aspects Of Activitymentioning
confidence: 63%
“…Additionally, the inhibitory effect of methyl, ethyl, isopropyl, and n -propyl esters of quinoxaline 1,4-di- N -oxide on Mycobacterium tuberculosis was assessed [ 62 ]. Of the 18 original esters of the 1,4-di- N -oxide synthesized, eight derivatives showed similar activity to that of isoniazid taken as reference ( Table 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compounds bearing a thioether linkage and a sterically bulky aromatic group at the terminal side chain on the C2 position are the best representatives of these original series. Additionally, the inhibitory effect of methyl, ethyl, isopropyl, and n-propyl esters of quinoxaline 1,4-di-N-oxide on Mycobacterium tuberculosis was assessed [62]. Of the 18 original esters of the 1,4-di-N-oxide synthesized, eight derivatives showed similar activity to that of isoniazid taken as reference (Table 12).…”
Section: Other Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Sekine et al reported that the presence and difference of the isopropyl group in a ring of p -menthane monoterpenoids affected termite mortality [ 37 ]. Several studies have reported that the isopropyl group in the compound has biological effects, such as anti-mycobacterial [ 38 , 39 ], anti-amoebic [ 40 ], and anticancer [ 39 ] activities. Therefore, the isopropyl group arrangement is important for the pharmacological activity of the compounds.…”
Section: Discussionmentioning
confidence: 99%